Growth hormone, gender and face shape in prader–willi syndrome. Issue 10 (5th August 2013) - de Souza, Mauren Abreu; McAllister, Catherine; Suttie, Michael; Perrotta, Concetta; Mattina, Teresa; Faravelli, Francesca; Forzano, Francesca; Holland, Anthony; Hammond, Peter
Abstract Prader–Willi syndrome is a neurodevelopmental disorder resulting from the absence of expression of paternally expressed gene(s) in a highly imprinted region of chromosome 15q11‐13. The physical phenotype includes evidence of growth retardation due to relative growth hormone deficiency, small hands and feet, a failure of normal secondary sexual development, and a facial appearance including narrow bifrontal diameter, almond‐shaped palpebral fissures, narrow nasal root, and thin upper vermilion with downturned corners of the mouth. Anecdotally, the face of individuals with PWS receiving hGH treatment is said to "normalize." We used dense surface modelling and shape signature techniques to analyze 3D photogrammetric images of the faces of 72 affected and 388 unaffected individuals. We confirmed that adults with Prader–Willi syndrome who had never received human growth supplementation displayed known characteristic facial features. Facial growth was significantly reduced in these adults, especially in males. We demonstrated that following human growth hormone (hGH) supplementation, vertical facial growth of affected individuals falls within the normal range. However, lateral and periorbital face shape and nose shape differences in affected children who have received hGH therapy remain sufficiently strong to be significantly discriminating in comparisons with age–sex matched, unaffected individuals. Finally, we produced evidence that age at initiation and length of treatment with hGH do not appear to play a role in normalization or in consistent alteration of the face shape of affected individuals. This is the first study to provide objective shape analysis of craniofacial effects of hGH therapy in Prader–Willi syndrome. © 2013 Wiley Periodicals, Inc.